A Depersonalised Object of Hope in a Funeral Sermon - Albín Masarik (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
In this article, the author calls attention to a danger of proclaiming a depersonalised object of hope in a Christian funeral sermon, which he does not consider to be a legiti- mate Christian practice. The author reached this conclusion based on his analysis of one particular sermon from his research sample of 3x50 funeral sermons from three different church traditions (Lutheran church, evangelical churches, and Roman Catholic church). In the aforementioned funeral sermon, the object of hope was found to be articulated in a depersonalised form – the hope is not the eternity with the Lord, but simply: heaven. Christ is, in this particular sermon, merely a means by which the hearers may obtain their desired goal. Even though this funeral sermon was formulated using Christian ter - minology and was delivered by a Christian preacher, the author of this article does not regard its fundamental approach as Christian.